Aplikasi Pembelajaran Pengenalan Bangun Datar Menggunakan Metode Invariant Moment - I Gusti Bagus Maha Putra; I Made Gede Sunarya; Made Windu Antara Kesiman (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
This research aims to design and develop an application inditifier of plane learning that can be used to facilitate for students  to recognize plane.This application is developed by using the invariant moment method .  The input of this application is an image of a user using a digital pen, touchpad or mouse , and the output are number and shape that have the smallest error value.. In this application there are two main processes namely preprocessing and recognition by euclidian distance. Preprocessing process consists of grayscale, edge detection, segmentation, cropping and 7 Hu moment. Hu defines 7 shape descriptors value, that is calculated from moment central through three degree of being free in translasi, the scale and direction of an object. Testing program conducted by two students of elementary school and eight student of junior high school, obtained results the average accuracy on elementary school students of 62.5% while in junior high school students  of 96,1 %.